Stakeholders’ perceptions of adolescents’ sexual and reproductive health needs in Southeast Nigeria: a qualitative study - Obinna Onwujekwe; Chinyere Cecilia Okeke; Chinyere Ojiugo Mbachu; Ifunanya Clara Agu; Uchenna Ezenwaka; Ifeyinwa Arize; Chibuike Agu; Chinonso Obayi (BMJ Open)
Objectives This study explored the perceptions of adult stakeholders on adolescents sexual and reproductive health (SRH) needs, variations of perceived needs by different social stratifiers and adolescent’s perceived interventions to address these needs. This will provide evidence that could be useful for policy and programme reviews for improving access and use of services in to meet the SRH needs of adolescents.Design A qualitative cross-sectional study was conducted in Ebonyi state, Southeast, Nigeria. Data were analysed using thematic framework and content analysis approaches.Setting and participants This qualitative study was conducted in six selected local government areas in Ebonyi state, Nigeria. The study participants comprised of adult stakeholders including community leaders, adolescent boys and girls aged 13–18 years. Adolescents were purposively selected from schools, skill acquisition centres and workplaces. A total of 77 in-depth interviews, 6 (with community leaders) and 12 (with adolescents) focus group discussions were conducted using pretested question guides.Results Adolescent SRH needs were perceived to be unique and special due to their vulnerability, fragility and predisposition to explore new experiences. Recurring adolescent SRH needs were: SRH education and counselling; access to contraceptive services and information. These needs were perceived to vary based on sex, schooling and marital status. Adolescent girls were perceived to have more psychological needs, and more prone to negative health outcomes. Out-of-school adolescents were described as more vulnerable, less controlled, less supervised and more prone to sexual abuse. Unmarried adolescents were perceived more vulnerable to sexual exploitation and risks, while married were perceived to have more maternal health service needs.Conclusions Perceptions of adolescents’ SRH needs converge among stakeholders (including adolescents) and are thought to vary by gender, schooling and marital status. This calls for well-designed gender-responsive interventions that also take into consideration other social stratifiers and adolescent’s perceived SRH intervention strategies.